A student's guide to coding and information theory - Moser, Stefan M.; Chen, Po-Ning (Cambridge University Press, 2012)
This guide provides an introduction to the engineering background of modern communication systems, from mobile phones to data compression and storage. The authors begin with many practical applications in coding, including the repetition code, the Hamming code and the Huffman code. They then explain the corresponding information theory, from entropy and mutual information to channel capacity and the information transmission theorem. Finally, they provide insights into the connections between coding theory and other fields. Many worked examples are given throughout the book, using practical applications to illustrate theoretical definitions. Exercises are also included, enabling readers to double-check what they have learned and gain glimpses into more advanced topics